Sympathy, Magnetism, and Immoderate Laughter: The Feather in Cook's Last Voyage. Issue 4 (2nd October 2019) - Pollitt, Ben
Abstract : A mysterious force capable of binding things as well as people together and a guiding moral principle, the concept of "sympathy" in the late eighteenth century blurred the boundaries between superstition and Enlightenment rationality. What light might this "sympathy" shed on James Cook's last voyage? What might it say about the induction of artifacts brought back from that voyage into European collections and, correspondingly, the contemporaneous introduction of "European" objects into Pacific cosmologies? Focusing on the materiality of these objects, specifically, the feather, allows us to explore the ways in which "sympathy" both unites and divides these heterogeneous archives.